Accretionary prism deformation and fluid migration caused by slow earthquakes in the Nankai subduction zone - T. Tonegawa; T. Akuhara; Y. Yamashita; Y. Yamashita; H. Sugioka; M. Shinohara; S. Takemura; T. Tsuji (Solid Earth)
Slow earthquakes induce structural deformation around their source regions and can also be linked to fluid migrations. Both of these phenomena potentially induce temporal variations in the seismic structure; how these two factors behave for a slow earthquake episode remains unknown. In this study, we applied the ambient noise correlation technique to the continuous records acquired at the seafloor in the Nankai subduction zone. We investigate the changes in seismic velocity (dv/v<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="26pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="99ece46ee778de24e04a64adf12fd536"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="se-16-579-2025-ie00001.svg" width="26pt" height="14pt" src="se-16-579-2025-ie00001.png"/></svg:svg>) and heterogeneous correlation coefficient (CC) structures before and after the slow earthquake activity that occurred around the shallow plate interface from the end of 2020. As a result, temporal variations in dv/v<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="26pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="a815a0a7fb4e240b0da07821157651cc"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="se-16-579-2025-ie00002.svg" width="26pt" height="14pt" src="se-16-579-2025-ie00002.png"/></svg:svg> and CC show different patterns for the slow earthquake episode. The dv/v<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="26pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="92bdba2ad42a292cf92722c48f8a5081"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="se-16-579-2025-ie00003.svg" width="26pt" height="14pt" src="se-16-579-2025-ie00003.png"/></svg:svg> variations show a step-like temporal reduction, and the reduced velocity was not recovered to the original level until the end of the observation period, whereas the CC variations show transient reductions and were recovered to the original level after the episode. Thus, the dv/v<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="26pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="649bb0a7d3baba33033ba2fc08e55fb3"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="se-16-579-2025-ie00004.svg" width="26pt" height="14pt" src="se-16-579-2025-ie00004.png"/></svg:svg> reflects the variation in the aspect ratio of pre-existing cracks and/or newly created cracks due to sediment deformation, where the extensional stresses normal to the trough were induced by the slips of the slow earthquakes, and the updated crack condition persisted even after the episode. We suggest that the CC variations correspond to transient fluid migrations from the source regions to shallow depths, activated by the fracturing of fluid caprocks that resulted from slow earthquakes. Our study indicates that monitoring these two quantities provides useful information to understand the variations in the subsurface structure due to slow earthquakes.